1871 Revision of the Statutes of New Jersey 232-33, An act for the punishment of crimes, II. Against the public peace, § 31 - (:unkn) unknown (General Publisher, 1877)
If any person shall by word, message, letter, or any other way, challenge another to fight a duel, with a rapier, or small-sword, back-sword, pistol, or other dangerous weapon, or shall accept a challenge, although not duel be fought, or knowingly be the bearer of such challenge, or shall any way abet, prompt, encourage, persuade, seduce, or cause any person to fight a duel, or to challenge another to fight a duel, every person so offending shall be deemed guilty of a misdemeanor
--
Keywords: DUELING